Application of Andersen’s behavioural model of health services use: a scoping review with a focus on qualitative health services research - Lederle, Mareike (BMJ Open, 2021)
INTRODUCTION: Qualitative methods have become integral in health services research, and Andersen’s behavioural model of health services use (BMHSU) is one of the most commonly employed models of health service utilisation. The model focuses on three core factors to explain healthcare utilisation: predisposing, enabling and need factors. A recent overview of the application of the BMHSU is lacking, particularly regarding its application in qualitative research. Therefore, we provide (1) a descriptive overview of the application of the BMHSU in health services research in general and (2) a qualitative synthesis on the (un)suitability of the model in qualitative health services research. METHODS: We searched five databases from March to April 2019, and in April 2020. For inclusion, each study had to focus on individuals ≥18 years of age and to cite the BMHSU, a modified version of the model, or the three core factors that constitute the model, regardless of study design, or publication type. We used MS Excel to perform descriptive statistics, and applied MAXQDA 2020 as part of a qualitative content analysis. RESULTS: From a total of 6319 results, we identified 1879 publications dealing with the BMSHU. The main methodological approach was quantitative (89%). More than half of the studies are based on the BMHSU from 1995. 77 studies employed a qualitative design, the BMHSU was applied to justify the theoretical background (62%), structure the data collection (40%) and perform data coding (78%). Various publications highlight the usefulness of the BMHSU for qualitative data, while others criticise the model for several reasons (eg, its lack of cultural or psychosocial factors). CONCLUSIONS: The application of different and older models of healthcare utilisation hinders comparative health services research. Future research should consider quantitative or qualitative study designs and account for the most current and comprehensive model of the BMHSU.